1976
DOI: 10.1016/s0022-5347(17)59108-9
|View full text |Cite
|
Sign up to set email alerts
|

Hematoporphyrin Derivative: A Possible Aid in the Diagnosis and Therapy of Carcinoma of the Bladder

Abstract: The distribution of hematoporphyrin derivative has been studied in patients undergoing transurethral resections and total cystectomy for carcinoma of the bladder. Although hematoporphyrin derivative fluorescence was not confined to malignant tissues with the dose used there was preferential localization in malignant and pre-malignant epithelium. Also high intensity illumination of an area of hematoporphyrin derivative sensitized carcinoma caused tumor destruction. Therefore, it is suggested that hematoporphyri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
121
0
9

Year Published

1981
1981
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 356 publications
(130 citation statements)
references
References 6 publications
0
121
0
9
Order By: Relevance
“…The tumoricidal effect of HpD following light exposure is generally attributed to the formation of singlet oxygen generated by the transfer of energy from the excited HpD to tissue oxygen (Weishaupt et al, 1976;Moan et al, 1979). While the reasons for the preferential accumulation of HpD in neoplastic tissue, and even the exact basis of its anti-tumour effects, remain to be elucidated it has been used in the treatment of human cancer (Kelly & Snell, 1976;Dougherty et al, 1979;Forbes et al, 1980;Hayata et al, 1980;Dahlman et al, 1983;Ha et al, 1983;Carruth et al, 1985). However, HpD has many characteristics which make it less than an ideal photosensitizer.…”
mentioning
confidence: 99%
“…The tumoricidal effect of HpD following light exposure is generally attributed to the formation of singlet oxygen generated by the transfer of energy from the excited HpD to tissue oxygen (Weishaupt et al, 1976;Moan et al, 1979). While the reasons for the preferential accumulation of HpD in neoplastic tissue, and even the exact basis of its anti-tumour effects, remain to be elucidated it has been used in the treatment of human cancer (Kelly & Snell, 1976;Dougherty et al, 1979;Forbes et al, 1980;Hayata et al, 1980;Dahlman et al, 1983;Ha et al, 1983;Carruth et al, 1985). However, HpD has many characteristics which make it less than an ideal photosensitizer.…”
mentioning
confidence: 99%
“…THE INTRODUCTION of haematoporphyrin derivative (HPD) as a selective tumour-seeking and photodynamically active agent has led to the development of a new treatment modality for cancer (Dougherty et al, 1976aKelly & Snell, 1976;Forbes et al, 1980). A selective effect of the treatment on malignant tissue has been demonstrated (Kelly et al, 1975).…”
mentioning
confidence: 99%
“…TIIE PHOTOI)YNAMIC EFFECT of porphyrins has been taken advantage of in recent successful clinical trials with photochemotherapy of cancer in the presence of haematoporphyrin derivative (HPD) (Kelly & Snell, 1976;Dougherty et al, 1978). In these and other studies a surprisingly rapid necrosis of solid tumours has been found.…”
mentioning
confidence: 99%